A feminist reading of debt - Cavallero, Lucí; Gago, Verónica 1976- (Mapping social reproduction theory, 2021)
In this sharp intervention, authors Lucí Cavallero and Verónica Gago defiantly develop a feminist understanding of debt, showing its impact on women and members of the LGBTQ+ community and examining the relationship between debt and social reproduction. Exploring the link between financial activity and the rise of conservative forces in Latin America, the book demonstrates that debt is intimately linked to gendered violence and patriarchal notions of the family. Yet, rather than seeing these forces as insurmountable, the authors also show ways in which debt can be resisted, drawing on concrete experiences and practices from Latin America and around the world. Featuring interviews with women in Argentina and Brazil, the book reveals the real-life impact of debt and how it falls mainly on the shoulders of women, from the household to the wider effects of national debt and austerity. However, through discussions around experiences of work, prisons, domestic labour, agriculture, family, abortion and housing, a narrative of resistance emerges. Quelle: Verlag